Washing machine related injuries in children: a continuing threat. Issue 4 (23rd December 2003) - Warner, B L; Kenney, B D; Rice, M
Abstract : Objective: To describe washing machine related injuries in children in the United States. Methods: Injury data for 496 washing machine related injuries documented by the Consumer Product Safety Commission's National Electronic Injury Surveillance System and death certificate data files were analyzed. Gender, age, diagnosis, body part injured, disposition, location and mechanism of injury were considered in the analysis of data. Results: The upper extremities were most frequently injured in washing machine related injuries, especially with wringer machines. Fewer than 10% of patients required admission, but automatic washers accounted for most of these and for both of the deaths. Automatic washer injuries involved a wider range of injury mechanism, including 23 children who fell from the machines while in baby seats. Conclusions: Though most injuries associated with washing machines are minor, some are severe and devastating. Many of the injuries could be avoided with improvements in machine design while others suggest a need for increased education of potential dangers and better supervision of children if they are allowed access to areas where washing machines are operating. Furthermore, washing machines should only be used for their intended purpose. Given the limitations of educational efforts to prevent injuries, health professionals should have a major role in public education regarding these seemingly benign household appliances.